2020
DOI: 10.1093/intqhc/mzaa139
|View full text |Cite
|
Sign up to set email alerts
|

International survey of COVID-19 management strategies

Abstract: Background While individual countries have gained considerable knowledge and experience in coronavirus disease of 2019 (COVID-19) management, an international, comparative perspective is lacking, particularly regarding the measures taken by different countries to tackle the pandemic. This paper elicits the views of health system staff, tapping into their personal expertise on how the pandemic was initially handled. Methods Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…Previous studies found that the interventions put in place during this period to address the impact of the pandemic on healthcare workers have been similar to those described here [22][23][24]. Psychological counseling and measures to prevent burnout have been described by professionals as the most common interventions to support them [25]. However, the professionals themselves decided to use the tools made available to them or did not consider it necessary for them.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies found that the interventions put in place during this period to address the impact of the pandemic on healthcare workers have been similar to those described here [22][23][24]. Psychological counseling and measures to prevent burnout have been described by professionals as the most common interventions to support them [25]. However, the professionals themselves decided to use the tools made available to them or did not consider it necessary for them.…”
Section: Discussionmentioning
confidence: 68%
“…The type of technology used to manage COVID-19 between the high-income and low-middle income countries was similar; however, Kenya and Rwanda had a more comprehensive approach when using novel technology. Studies evaluating the technical efficiency and overall performance of national COVID-19 management have consistently criticized the United Kingdom and Canada as underperforming despite having access to exceptional resources [ 31 - 33 ]. In fact, the Lowy Institute assessed the performance during the first wave of 98 countries by evaluating various parameters including confirmed cases and deaths per million people and confirmed the cases as a proportion of tests [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 Australian Institute of Health Innovation, Macquarie University, Sydney, NSW, Australia. 4 Department of Global Health and Development, Faculty of Public Health and Policy, London School of Hygiene and Tropical Medicine, London, UK. 5 Institute for Women and Children's Health, King's College London, London, UK.…”
Section: Ethical Issuesmentioning
confidence: 99%